Interpersonal goals and change in anxiety and dysphoria in first-semester college students. [article]. - Crocker, Jennifer
Two longitudinal studies examined the associations between interpersonal goals (i.e., self-image and compassionate goals) and anxiety and dysphoria (i.e., distress). In study 1 199 college freshmen (122 women, 77 men) completed 12 surveys over 12 weeks. Compassionate goals predicted decreased distress, and self-image goals predicted increase distress from pretest to post test when distress was assessed as anxiety, dysphoria, or a composite, and when the goals were worded as approach goals, avoidance goals, or a composite. In study 2, 115 first-semester roommate pairs (86 female and 29 male pairs) completed 12 surveys over 12 weeks. Compassionate and self-image goals predicted distress in same-week, lagged-week, and pretest-to -posttest analyses; effects of compassionate goals remained significant when the authors controlled for several known risk factors. Having clear goals consistently explained the association between compassionate goals but not self-image goals and distress. Results supported a path mo0del in which compassionate goals predict increased support given to roommates, which predicts decreased distress. Result also supported a reciprocal association, chronic distress predicted decreased compassionate and increased self-image goals from pretest to posttest, and weekly distress predicted decreased compassionate goals the subsequent week. The results suggest that compassionate goals contribute to decreased distress because they provide meaning and increase support to others. Distress, in turn,predicts change in goals, creating the potential for upward and downward spirals of goals and distress.